Penerapan Media Promosi Umkm Fataya Ecoprint - Robi Ahmad Dans; Yoni Sudiani (VisArt: Jurnal Seni Rupa dan Design, 2025)
Micro, Small and Medium Enterprises (MSMEs) and Small and Medium Enterprises (SMEs) have tremendous importance in the Indonesian economy. Although MSMEs have shown their role in the national economy, there are obstacles when they try to grow which is influenced by the absence of promotional media channels in marketing products, resulting in a decrease in sales. Fataya ecoprint MSMEs have problems regarding the promotional needs of Fataya ecoprint. This research aims to design promotional media for Fataya ecoprint MSMEs that present the value of Fataya ecoprint which has the concept of Be ur self be natural, so that it can change the perception of consumers by utilizing social media, it is hoped that Fataya ecoprint MSMEs can reach a wider market, increase sales, and strengthen brand image in the community. The design of promotional media for Fataya ecoprint MSMEs uses data collection methods in the form of observations, interviews, and online questionnaires and the data analysis methods used are SWOT and USP analysis with the target audience covering all people inside and outside Sijunjung. The results of this design are in the form of Social Media Content and Audio Visual, with supporting media in the form of Posters, X-Banners, Flyers, Stickers, and Catalogs.